LATAH: A CLINICAL LINGUISTIC REVIEW - Ahmad Mubarok; Faisal Rahman; Fajrianor Fajrianor (LET: Linguistics, Literature and English Teaching Journal, 2020)
This study describes the speech disorder in latah patients in terms of phonology with the Clinical Linguistic approach. Latah is a linguistic behaviour that occurs when someone is shocked, accidentally issuing words spontaneously and not aware of what he/she is saying. The the subjects of the study were severe latah sufferers namely latah echolalia, coprolalia, and automatic obedience, totalling 3 people. The words spoken by latah sufferers become research material and are reviewed from the phonological aspect in a clinical linguistic perspective. The main requirement for latah people is shock. Latah sufferers should be valued more. The surrounding environment has an important role for the recovery of latah sufferers because basically latah sufferers are caused by the surrounding environment. To reduce and cure latah, sufferers must find peace of life. The rest, the sufferers are encouraged to do relaxation exercises, meditation, and concentration on a regular basis. This activity will help sufferers to recovery.